Preparation method of diffusion barrier layer for three-dimensional packaging

The diffusion barrier layer is prepared by high-entropy alloy, forming multi-element intermetallic compounds and converting them into Cu3Sn, solving the problem of limited barrier effects in the prior art, and achieving efficient and long-term Cu diffusion barrier and electrical conductivity improvement.

CN119446926BActive Publication Date: 2025-03-21HUAMAO ZHIXIN INTEGRATED ELECTRONICS (JIANGSU) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510031670.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-21
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The barrier effect of the diffusion barrier layer prepared in the prior art is limited, and it is difficult to meet the reliability requirements of fine-pitch solder joints in three-dimensional packaging.

Method used

A high-entropy alloy is used to prepare a diffusion barrier layer. Through processes such as smelting, rolling, cutting, ball reflux and hot press bonding, multi-element intermetallic compounds (MEIMCs) are formed, and completely converted into Cu3Sn under hot pressing conditions to avoid the formation of Kirkendal cavity.

Benefits of technology

It effectively and efficiently blocks Cu diffusion, extends service life, improves conductive and mechanical properties, and ensures the reliability of three-dimensional packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119446926B_ABST
    Figure CN119446926B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of semiconductor three-dimensional packaging technology, in particular, to a preparation method for a diffusion barrier layer for three-dimensional packaging, which includes: melting a high entropy alloy, the high entropy alloy having a face-centered cubic structure; rolling the high entropy alloy, the total reduction is 80-90%, annealing at the recrystallization temperature of the high entropy alloy after rolling, and air cooling; cutting to obtain a high entropy alloy patch with a thickness of 1-3 μm; melting the tin ball by a ball planting reflow method, and fusing it with a copper column to form a solder ball; hot-pressing the high entropy alloy patch and the solder ball under hot pressing conditions, the temperature of the hot pressing bonding is 250-270 ° C, the pressure is 200-300 gf, and the time is 20-30 min. The diffusion barrier layer obtained by the preparation method has a good barrier effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor three-dimensional packaging, and in particular to a method for preparing a diffusion barrier layer used for three-dimensional packaging. Background Art

[0002] Solder joints play an important role in electronic packaging, serving as both electrical interconnects between components and mechanical support for components. As electronic packaging continues to shrink in size and become more integrated, fine-pitch solder joints are required, so the reliability of solder joints becomes more critical. In related technologies, a barrier layer is usually grown on the substrate through PVD (physical vapor deposition) to improve the reliability of solder joints.

[0003] However, the barrier effect of the barrier layer produced by the related technology is limited. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing a diffusion barrier layer for three-dimensional packaging. The diffusion barrier layer obtained by the preparation method has a good barrier effect.

[0005] The present invention is achieved in that:

[0006] The present invention provides a method for preparing a diffusion barrier layer for three-dimensional packaging, comprising:

[0007] Melting high entropy alloy, high entropy alloy has face-centered cubic structure;

[0008] Rolling the high entropy alloy with a total reduction of 80-90%, annealing at the recrystallization temperature of the high entropy alloy after rolling, and air cooling;

[0009] Cutting to obtain a high entropy alloy patch with a thickness of 1-3 μm;

[0010] The solder ball is melted by the ball planting reflow method and welded with the copper pillar of the chip to form a solder ball;

[0011] The high entropy alloy patch and the solder ball are hot-pressed and bonded under hot-pressing conditions, wherein the hot-pressing bonding temperature is 250-270° C., the pressure is 200-300 gf, and the time is 20-30 minutes.

[0012] In an optional embodiment, the rolling method includes: hot rolling after keeping at 800-900° C., and the deformation of a single pass is 15-20%.

[0013] In an optional embodiment, the annealing time is 0.8~1.2h.

[0014] In an optional embodiment, the degree of vacuum during smelting is greater than or equal to 10 -3 Pa, and inert gas is used as the protective gas for smelting.

[0015] In an optional embodiment, the thickness of the high entropy alloy patch is less than 2 μm.

[0016] In an optional embodiment, the reflow peak temperature of the ball planting reflow is 235-250° C., and the peak holding time is 30-50 s.

[0017] In an optional embodiment, the heating rate of the ball planting reflow is 1-5° C. / s.

[0018] In an optional embodiment, the cooling rate of the ball planting reflow is greater than 5° C. / s.

[0019] In an alternative embodiment, the height of the solder ball is less than or equal to 5 μm.

[0020] In an optional embodiment, the high entropy alloy includes at least four of aluminum Al, copper Cu, cobalt Co, chromium Cr, iron Fe, manganese Mn, nickel Ni, titanium Ti, and vanadium V.

[0021] The present invention has the following beneficial effects:

[0022] The method for preparing a diffusion barrier layer for three-dimensional packaging provided by an embodiment of the present invention uses a high entropy alloy to prepare the diffusion barrier layer. The high entropy alloy reacts with Sn to form a MEIMC (multi-element intermetallic compound). Since the high entropy alloy itself has good stability, the growth rate of the formed MEIMC is very slow, and the thickness changes slightly with time. As a diffusion barrier layer, it can reliably and long-term block the diffusion of Cu and extend the service life.

[0023] Moreover, after hot pressing bonding, the intermetallic compound layer between the high entropy alloy and the copper pillar is completely converted into Cu3Sn. Specifically, under the condition of temperature of 250~270℃ and hot pressing for 20~30s, the diffusion and mobility of Cu atoms and Sn atoms are enhanced, and the reaction of Cu and Sn is accelerated. Under the action of pressure, the atoms diffuse and move to the area where voids or vacancy defects are concentrated, and completely react to generate Cu3Sn. That is, the Kirkendall voids generated under the action of pressure and molecular thermal motion are gradually healed, so that the diffusion barrier layer will not generate Kirkendall voids, further ensuring the good barrier effect of the high entropy alloy barrier layer.

[0024] Furthermore, the thickness of the high entropy alloy patch is relatively thin, which has little effect on the conductivity, thus improving the problem of increased resistivity and reduced conductivity.

[0025] Annealing at the recrystallization temperature after rolling can cause the high entropy alloy to undergo a recovery process, in which point defects migrate, dislocations move and redistribute, reducing the point defect concentration and dislocation density. The lattice distortion caused by point defects will cause the conduction electrons to scatter, and similarly, dislocations will also produce scattering effects. Therefore, reducing the number of both can reduce the resistivity and improve the conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0027] Figure 1 is a schematic diagram of a chip according to Embodiment 1 of the present invention;

[0028] Figure 2 Schematic diagram of the ball planting reflow temperature time curve of Example 1 of the present invention;

[0029] Figure 3 This is a bonding schematic diagram of Example 1 of the present invention;

[0030] Figure 4 This is a schematic diagram of the structure of other chips in Experimental Example 1 of the present invention;

[0031] Figure 5 This is a scanning electron microscope image of the fracture morphology of the detection experiment of Example 1 of the present invention;

[0032] Figure 6 This is a scanning electron microscope image of the fracture morphology of the detection experiment of comparative example 8 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0034] The present disclosure provides a method for preparing a diffusion barrier layer for three-dimensional packaging, which comprises:

[0035] Melting high entropy alloy, high entropy alloy has face-centered cubic structure;

[0036] Rolling the high entropy alloy with a total reduction of 80-90% (e.g., 80%, 82%, 85%, 88%, 90%, etc., not specifically limited herein), annealing at the recrystallization temperature of the high entropy alloy after rolling, and air cooling;

[0037] Cutting to obtain a high entropy alloy patch with a thickness of 1-3 μm (for example, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, 2.1 μm, 2.5 μm, 3 μm, etc., not specifically limited herein);

[0038] The solder ball is melted by the ball planting reflow method and welded with the copper pillar of the chip to form a solder ball;

[0039] The high entropy alloy patch and the solder ball are hot-pressed and bonded under hot-pressing conditions, the hot-pressing bonding temperature is 250-270°C (for example, 250°C, 255°C, 260°C, 265°C, 270°C, etc., not specifically limited here), the pressure is 200-300gf (for example, 200gf, 220gf, 240gf, 270gf, 300gf, etc., not specifically limited here), and the time is 20-30min (for example, 20min, 22min, 24min, 26min, 28min, 30min, etc., not specifically limited here).

[0040] The diffusion barrier layer is prepared by high entropy alloy. The high entropy alloy will react with Sn to form MEIMC (multi-element intermetallic compound). Since the high entropy alloy itself has good stability, the growth rate of the formed MEIMC is very slow, and the thickness changes slightly with time. As a diffusion barrier layer, it can reliably and long-term block the diffusion of Cu and extend the service life.

[0041] Moreover, after hot pressing bonding under hot pressing conditions, the intermetallic compound layer between the high entropy alloy and the copper pillar is completely converted into Cu3Sn. Specifically, at a temperature of 250~270℃ and hot pressing for 20~30s, the diffusion and mobility of Cu atoms and Sn atoms are enhanced, and the reaction of Cu and Sn is accelerated. Under the action of pressure, the atoms diffuse and move to the area where the voids or vacancy defects are concentrated, and completely react to generate Cu3Sn. That is, the Kirkendall voids generated under the action of pressure and molecular thermal motion are gradually healed, so that the diffusion barrier layer will not generate Kirkendall voids, further ensuring the good barrier effect of the high entropy alloy barrier layer.

[0042] Furthermore, the thickness of the high entropy alloy patch is relatively thin, which has little effect on the conductivity, thus improving the problem of increased resistivity and reduced conductivity.

[0043] Annealing at the recrystallization temperature after rolling can cause the high entropy alloy to undergo a recovery process, in which point defects migrate, dislocations move and redistribute, reducing the point defect concentration and dislocation density. The lattice distortion caused by point defects will cause the conduction electrons to scatter, and similarly, dislocations will also produce scattering effects. Therefore, reducing the number of both can reduce the resistivity and improve the conductivity.

[0044] It should be noted that the reason for the formation of Kirkendall voids is that the unbalanced diffusion of atoms increases the number of atoms on one side of the interface, while the number of atoms on the other side decreases or the number of vacancies increases. The generated vacancies will continue to gather at the interface or dislocation. Once the vacancy concentration reaches supersaturation, the voids begin to nucleate and grow. At 250-270°C, the diffusion and mobility of Cu and Sn atoms are enhanced, and the reaction of Cu and Sn is accelerated. Under the pressure of hot pressing, the atoms diffuse and move to the area where voids or vacancy defects are concentrated. Cu3Sn can be completely reacted within 20-30 minutes without Kirkendall voids.

[0045] Optionally, the rolling method includes: hot rolling after keeping warm at 800-900°C (for example, 800°C, 820°C, 850°C, 870°C, 900°C, etc., not specifically limited herein), the keeping time is 0.8~1.2h (for example, 0.8h, 0.9h, 1.0h, 1.1h, 1.2h, etc., not specifically limited herein); the deformation amount of a single pass is 15~20% (for example, 15%, 16%, 17%, 18%, 19%, 20%, etc., not specifically limited herein).

[0046] After heating, the diffusion and movement of atoms in the alloy are enhanced, dislocation movement and redistribution occur, dislocation density is reduced, part of the internal stress is eliminated, plasticity is improved, deformation resistance is low, and formability is good, and cracks are not easy to occur after rolling. Specifically, 1. During rolling, the alloy undergoes a dynamic recovery mechanism under the action of temperature and rolling, that is, external stress: as the strain increases, dislocations proliferate, their density continues to increase, and dislocation entanglement and cellular substructures begin to form; however, due to the high temperature, thermal activation conditions are provided for the recovery process, through the climb of edge dislocations, cross-slip of screw dislocations, depinning of dislocation nodes, and subsequent cancellation of dislocations of opposite signs on the new slip plane, the dislocation density is continuously reduced; in this process, dislocations continue to proliferate and disappear, which can eliminate defects such as pores and looseness during rolling, improve the shape, size and distribution of inclusions and brittle materials; and can eliminate part of the segregation, refine and uniform the grains, and improve the mechanical properties, corrosion resistance and thermal stability of high entropy alloys. 2. After rolling, various point defects of the alloy are reduced, which inhibits the diffusion rate of interstitial diffusion mechanism and vacancy diffusion mechanism that require point defects to provide diffusion media. The slip plane and slip direction of each grain of the high-entropy alloy must rotate toward the main deformation direction, and the crystal plane and crystal direction also tend to be parallel to the rolling direction, forming a deformation texture; therefore, the number of diffusion channels perpendicular to the rolling direction is reduced, and the diffusion of atoms is inhibited; after the rolled high-entropy alloy is bonded to the copper column, the diffusion of elements on both sides will be well inhibited.

[0047] Optionally, the annealing time is 0.8-1.2 h, for example, 0.8 h, 0.9 h, 1.0 h, 1.1 h, 1.2 h, etc., which is not specifically limited here.

[0048] Optionally, the high entropy alloy includes at least four of aluminum Al, copper Cu, cobalt Co, chromium Cr, iron Fe, manganese Mn, nickel Ni, titanium Ti, and vanadium V, and is designed and configured in an equiatomic ratio or a nearly equiatomic ratio to produce a high entropy alloy with FCC (face-centered cubic structure) as a single phase or FCC as the main phase through a vacuum induction melting process.

[0049] Optionally, the degree of vacuum during smelting is greater than or equal to 10 -3 Pa, and an inert gas is used as the protective gas for the smelting, and the inert gas includes but is not limited to argon Ar.

[0050] When the related technology uses the PVD (physical vapor deposition) process to deposit Ni as a barrier layer, the Ni layer needs to be at least 2μm thick to ensure an effective barrier effect. Moreover, the barrier effect of the Ni layer continues to weaken over time.

[0051] The inventors found that after reflow at 250°C for 60 minutes, the Cu element of the copper column will diffuse through the Ni barrier layer, and the Ni barrier layer can no longer provide an effective blocking effect; however, a high-entropy alloy with a thickness of less than 2 μm can still block the diffusion of the Cu element after reflow at a high temperature of 250°C for 60 minutes.

[0052] Optionally, the reflow peak temperature of the ball planting reflow is 235~250℃ (for example: 235℃, 240℃, 245℃, 250℃, etc., not specifically limited here), and the peak holding time is 30~50s (for example: 30s, 35s, 40s, 45s, 50s, etc., not specifically limited here).

[0053] Furthermore, the heating rate of the ball planting reflow is 1~5℃ / s (for example: 1℃ / s, 2℃ / s, 3℃ / s, 4℃ / s, 5℃ / s, etc., not specifically limited here); the cooling rate of the ball planting reflow is greater than 5℃ / s (for example: 5.5℃ / s, 6℃ / s, 6.5℃ / s, etc., not specifically limited here).

[0054] Furthermore, the height of the solder ball is less than or equal to 5 μm, for example, 5 μm, 4 μm, 3 μm, etc., which is not specifically limited here.

[0055] Optionally, the chip surface may be pretreated before the ball implantation reflow process to remove contaminants; after the pretreatment, there are no particles larger than 1 μm and no organic residue on the surface. The pretreatment method includes, but is not limited to, plasma treatment and deionized water cleaning.

[0056] The present invention is further described in detail below in conjunction with embodiments.

[0057] Example 1

[0058] Melting high entropy alloy: High entropy alloy includes Fe, Co, Ni, and Cu in equal atomic ratios. During melting, the vacuum degree of the vacuum induction melting furnace is controlled to 10 -3 Pa, and filled with argon for protection; the high entropy alloy obtained by smelting is a FCC single phase.

[0059] Rolling high entropy alloy: hot rolling after keeping at 850℃ for 1h, the single pass deformation of rolling is 17%, and the total reduction is 85%; after rolling, annealing at the recrystallization temperature of the high entropy alloy for 1h and air cooling.

[0060] Wire cutting obtained a high entropy alloy patch with a thickness of 1 μm and the same diameter as the copper column.

[0061] Ball reflow: transfer the flux to the copper pillar, and place the solder ball on the copper pillar with flux. Through reflow soldering, high temperature is used to melt the solder ball and fuse the copper pillar into solder ball. The peak reflow temperature is 250℃, the peak temperature is kept for 40s, the heating rate is 5℃ / s, and the cooling rate is 6℃ / s. The height after reflow is 5μm. The copper pillars on the chip are distributed in a row. Figure 1 ; See the schematic diagram of the ball planting reflow temperature time curve Figure 2 .

[0062] The high-entropy alloy patch (HEA) and the solder ball are heat-pressed and bonded under hot-pressing conditions. The temperature of the hot-pressing bonding is 250°C, the pressure is 300gf, and the time is 30min. The schematic diagram after bonding is shown in Figure 3 .

[0063] Example 2

[0064] Melting high entropy alloy: High entropy alloy includes Al, Cu, Ni, Co, Fe, Ti, and V in equal atomic ratios. During melting, the vacuum degree of the vacuum induction melting furnace is controlled to 10 -2 Pa, and filled with argon for protection; the high entropy alloy obtained by smelting has FCC as the main phase.

[0065] Rolling high entropy alloy: hot rolling after keeping at 800℃ for 1.2h, the single pass deformation of rolling is 20%, and the total reduction is 80%; after rolling, annealing at the recrystallization temperature of the high entropy alloy for 1.2h and air cooling.

[0066] Wire cutting obtained a high entropy alloy patch with a thickness of 1.5μm and the same diameter as the copper column.

[0067] Ball planting reflow: The flux is transferred to the copper pillar, and the mold places the solder ball on the copper pillar with flux. Through reflow soldering, the high temperature is used to melt the solder ball and fuse the copper pillar into a solder ball; the reflow peak temperature is 235℃, the peak temperature is kept for 50s, the heating rate is 1℃ / s, and the cooling rate is 5.5℃ / s; the height after reflow is 4μm.

[0068] The high entropy alloy patch and the solder ball are bonded under hot pressing conditions, and the hot pressing bonding temperature is 270° C., the pressure is 200 gf, and the time is 20 minutes.

[0069] Example 3

[0070] Melting high entropy alloy: High entropy alloy includes Fe, Co, Ni, and Cu in equal atomic ratios. During melting, the vacuum degree of the vacuum induction melting furnace is controlled to 10 -2 Pa, and filled with argon for protection; the high entropy alloy obtained by smelting is a FCC single phase.

[0071] Rolling high entropy alloy: hot rolling after keeping at 900℃ for 0.8h, the single-pass deformation of rolling is 15%, and the total reduction is 90%; after rolling, annealing at the recrystallization temperature of the high entropy alloy for 0.8h and air cooling.

[0072] Wire cutting obtained a high entropy alloy patch with a thickness of 1.8μm and the same diameter as the copper column.

[0073] Ball planting reflow: The flux is transferred to the copper pillar, and the mold places the solder ball on the copper pillar with flux. Through reflow soldering, the high temperature is used to melt the solder ball and fuse the copper pillar into a solder ball; the reflow peak temperature is 240℃, the peak temperature is kept for 30s, the heating rate is 3℃ / s, and the cooling rate is 5.5℃ / s; the height after reflow is 3μm.

[0074] The high entropy alloy patch and the solder ball are bonded under hot pressing conditions, and the hot pressing bonding temperature is 260° C., the pressure is 250 gf, and the time is 25 minutes.

[0075] Example 4

[0076] The difference between Example 4 and Example 1 is that the thickness of the high entropy alloy patch is 2 μm, and other process parameters refer to Example 1.

[0077] Example 5

[0078] The difference between Example 5 and Example 1 is that the thickness of the high entropy alloy patch is 3 μm, and other process parameters refer to Example 1.

[0079] Comparative Example 1

[0080] The difference between Comparative Example 1 and Example 1 is that the high entropy alloy is rolled after being kept at 700° C. for 1 hour, and other process parameters refer to Example 1.

[0081] Comparative Example 2

[0082] The difference between Comparative Example 2 and Example 1 is that the high entropy alloy is rolled after being kept at 1000° C. for 1 hour, and other process parameters refer to Example 1.

[0083] Comparative Example 3

[0084] The difference between Comparative Example 3 and Example 1 is that the step of annealing at the recrystallization temperature after rolling is eliminated, and other process parameters refer to Example 1.

[0085] Comparative Example 4

[0086] The difference between Comparative Example 4 and Example 1 is that the thickness of the high entropy alloy patch is 0.5 μm, and other process parameters refer to Example 1.

[0087] Comparative Example 5

[0088] The difference between Comparative Example 5 and Example 1 is that the thickness of the high entropy alloy patch is 4 μm, and other process parameters refer to Example 1.

[0089] Comparative Example 6

[0090] The difference between Comparative Example 6 and Example 1 is that the temperature of the hot pressing bonding is 240° C., and the other process parameters refer to Example 1.

[0091] Comparative Example 7

[0092] The difference between Comparative Example 7 and Example 1 is that the temperature of the hot pressing bonding is 280° C., and the other process parameters refer to Example 1.

[0093] Comparative Example 8

[0094] The difference between Comparative Example 8 and Example 1 is that Ni is used to replace the high entropy alloy patch, and other process parameters refer to Example 1.

[0095] Experimental Example 1

[0096] The chips of Example 1 and Comparative Example 8 were soldered with pure Sn as solder under the same conditions as other chips (see Figure 4 , the copper pillars of the chip are sequentially provided with a Ni layer and a SnAg bump) bonding, and then a temperature cycle test and a shear test are performed to detect the barrier effect and reliability of the barrier layer of Example 1 and Comparative Example 8. Temperature cycle test conditions: -55°C ~ 125°C cycle once every hour, and the average growth thickness of the IMC is measured after 500 cycles. The test results are shown in Tables 1 and 2.

[0097] Table 1 Average growth thickness of IMC

[0098]

[0099] It can be seen from Table 1 that the barrier effect of the high entropy alloy is much better than that of the Ni barrier layer, about 3.9 times that of the Ni barrier layer. The high entropy alloy significantly inhibits the growth of the IMC layer.

[0100] Table 2 Shear strength

[0101]

[0102] It can be seen from Table 2 that the shear strength of the two barrier layers is basically the same. Figure 5 and Figure 6 The scanning electron microscope fracture morphology analysis shows that the morphology of the two is basically the same, both have dimples, and are ductile fractures. The fracture did not occur in the hard and brittle phase region of the IMC. Therefore, the bonding strength of the high entropy alloy fully meets the chip reliability requirements.

[0103] Experimental Example 2

[0104] The samples of Examples 1-5 and Comparative Examples 1-7 were subjected to temperature cycle tests and shear tests to detect the barrier effect and reliability of the barrier layer; wherein, the temperature cycle test: -55°C~125°C was cycled once every hour, and the average growth thickness of the IMC was measured after 500 cycles. The results are shown in Table 3.

[0105] Table 3

[0106]

[0107] According to Table 3 and the comparison of Examples 1-5, it can be seen that when the thickness of the high entropy alloy patch is greater than or equal to 2 μm, it still has a good diffusion barrier effect, but the shear strength is slightly poor.

[0108] By comparing Example 1 and Comparative Examples 1-2, it can be seen that rolling the high entropy alloy at a suitable temperature can improve the diffusion barrier effect and shear strength.

[0109] Comparing Example 1 with Comparative Example 3, it can be seen that the annealing step can improve the diffusion barrier effect and shear strength.

[0110] Comparing Example 1 with Comparative Examples 4 and 5, it can be seen that if the thickness of the high entropy alloy patch is too thin or too thick, it is impossible to ensure both a good diffusion barrier effect and shear strength.

[0111] Comparing Example 1 with Comparative Examples 6 and 7, it can be seen that too high or too low bonding temperature cannot improve the diffusion barrier effect and shear strength.

[0112] Experimental Example 3

[0113] The resistances of Examples 1-5 and Comparative Example 5 were tested, and the results are shown in Table 4.

[0114] Table 4

[0115]

[0116] According to Table 4, a high entropy alloy patch that is too thick will lead to a significant increase in resistance.

[0117] In summary, the method for preparing a diffusion barrier layer for three-dimensional packaging of the present invention does not produce Kirkendall voids, has good thermal stability, has high adhesion to the substrate, and has good mechanical properties such as shear tensile strength. The thickness of the IMC layer (intermetallic compound) changes slightly over time, which greatly prolongs the service life. Moreover, the preparation method is simple, does not require the use of large-scale equipment such as PVD, can effectively save costs, and is easy to mass produce.

[0118] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a diffusion barrier layer for three-dimensional packaging, characterized in that: include: Melting a high entropy alloy, wherein the high entropy alloy has a face-centered cubic structure; Rolling the high entropy alloy with a total reduction of 80-90%, annealing at the recrystallization temperature of the high entropy alloy after rolling, and air cooling; Cutting to obtain a high entropy alloy patch with a thickness of 1-3 μm; The solder ball is melted by the ball planting reflow method and welded with the copper pillar of the chip to form a solder ball; The high entropy alloy patch and the solder ball are heat-pressed and bonded under heat-pressing conditions, wherein the heat-pressing bonding temperature is 250-270° C., the pressure is 200-300 gf, and the time is 20-30 minutes.

2. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The rolling method comprises: hot rolling after keeping warm at 800-900°C, with a deformation amount of 15-20% in a single pass.

3. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The annealing time is 0.8~1.2h.

4. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The vacuum degree of the smelting is greater than or equal to 10 -3 Pa, and an inert gas is used as the protective gas for the smelting.

5. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The thickness of the high entropy alloy patch is less than 2 μm.

6. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The reflow peak temperature of the ball planting reflow is 235-250° C., and the peak holding time is 30-50 seconds.

7. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The heating rate of the ball planting reflow is 1-5°C / s.

8. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The cooling rate of the ball planting reflow is greater than 5°C / s.

9. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The height of the solder ball is less than or equal to 5 μm.

10. The method for preparing a diffusion barrier layer for three-dimensional packaging according to claim 1, characterized in that: The high entropy alloy includes at least four of aluminum, copper, cobalt, chromium, iron, manganese, nickel, titanium, and vanadium.

Citation Information

Patent Citations

  • Wafer-level glass ball cavity package method for light emitting diode flip chip

    CN102044621A

  • Solid-state hot-compression low-temperature bonding method using nickel micro needle cones

    CN102543784A